Quality selection, sectoral heterogeneity and Chinese exports - Kneller, Richard; Yu, Zhihong (Wiley, 2016)
Recent models of international trade have identified product quality as an important determinant of bilateral trade flows. In this paper we examine the relationship between the characteristics of the export market and the aggregate quality of products using Chinese data. We find evidence that product unit values vary with standard gravity variables in a different manner across sectors of the Chinese economy, and run contrary to earlier findings for the U.S. These results are not compatible with existing heterogeneous firm trade models with constant mark-up such as Melitz (2003) model and its extension to include product quality by Baldwin and Harrigan (2011). We construct a heterogeneous firm trade model with quality differences as in Baldwin and Harrigan (2011) and spatial price discrimination based on Melitz and Ottaviano (2008), and show that the model provides plausible explanations for our empirical finds as well as other existing findings in the literature.